2009
DOI: 10.1002/btpr.116
|View full text |Cite
|
Sign up to set email alerts
|

C. botulinum inactivation kinetics implemented in a computational model of a high‐pressure sterilization process

Abstract: High-pressure, high-temperature (HPHT) processing is effective for microbial spore inactivation using mild preheating, followed by rapid volumetric compression heating and cooling on pressure release, enabling much shorter processing times than conventional thermal processing for many food products. A computational thermal fluid dynamic (CTFD) model has been developed to model all processing steps, including the vertical pressure vessel, an internal polymeric carrier, and food packages in an axis-symmetric geo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2010
2010
2012
2012

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(32 citation statements)
references
References 38 publications
0
32
0
Order By: Relevance
“…Immediately available to commercialize PATP technology, is alternative (c) in Table 2, i.e., temperatures above 100°C to inactivate bacterial spores in a reasonably short time. The limitation of this alternative is the need for research on reaction kinetics in the pressure and temperature range required for this alternative, a severe limitation at this time (Ramírez and Torres 2009;Torres et al 2009b;Martínez Monteagudo et al 2011;Valdez-Fragoso et al 2010) when compared to the large availability of data on the inactivation of bacterial spores (Reddy et al 2003;Margosch et al 2004Margosch et al , 2006aRajan et al 2006;Ahn et al 2007a,b;Paredes-Sabja et al 2007;Naim et al 2008;Zhu et al 2008;Juliano et al 2009;Ratphitagsanti et al 2009). …”
Section: Inactivation Of Bacterial Sporesmentioning
confidence: 96%
“…Immediately available to commercialize PATP technology, is alternative (c) in Table 2, i.e., temperatures above 100°C to inactivate bacterial spores in a reasonably short time. The limitation of this alternative is the need for research on reaction kinetics in the pressure and temperature range required for this alternative, a severe limitation at this time (Ramírez and Torres 2009;Torres et al 2009b;Martínez Monteagudo et al 2011;Valdez-Fragoso et al 2010) when compared to the large availability of data on the inactivation of bacterial spores (Reddy et al 2003;Margosch et al 2004Margosch et al , 2006aRajan et al 2006;Ahn et al 2007a,b;Paredes-Sabja et al 2007;Naim et al 2008;Zhu et al 2008;Juliano et al 2009;Ratphitagsanti et al 2009). …”
Section: Inactivation Of Bacterial Sporesmentioning
confidence: 96%
“…The rapid heating and cooling in HPT processing offers the potential for producing high-quality shelf-stable products, including improved colour, flavour, and nutrient retention [1,6,11,15] compared to traditionally thermally processed products. Despite the fact that pressure is uniformly distributed throughout the pressure vessel in HPT processing, temperature is not [7,8]. The development of temperature gradients in HPT processing is a result of the differences in compression heating of the materials involved, i.e.…”
Section: Introductionmentioning
confidence: 97%
“…Such nonuniform transient temperature distributions are aggravated by any temperature mismatch of the incoming compression fluid (which may comprise up to about 20% of the vessel's volume). Various heat retention aids, including internal electrical heaters and polymeric insulating product baskets, have been proposed to counteract the cooling caused by the vessel walls, and the performance of some of these has been assessed [7][8][9]. However, the issue of temperature gradients in HPT processing is likely to remain, as it also remains in traditional thermal retort processes.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Pressure is the predominant process parameter for the inactivation kinetics of vegetative cells in high pressure pasteurization applications; therefore, non-uniformity of the process field is limited. However, studies on the inactivation of spores under high pressure-high temperature conditions showed that temperature becomes a determining variable [13,72,73,152]. For process optimization purposes, the detection of the point of the lowest and higher impact is necessary to verify the effects of the treatment on safety and quality features.…”
Section: Process Optimizationmentioning
confidence: 99%